SHOULD ROMANIANS BE CONCERNED WITH THE ASBESTOS BURDEN? RESEARCH OVERVIEW AND CONTEXT - Gabriela MUNTEANU (Studia Universitatis Babeş-Bolyai: Geographia, 2021)
Although the negative effects of airborne asbestos fibers upon human health had been known for a long time, asbestos was widely used all over the world. Between 1980 and 2010, many countries have banned asbestos production and trade; among them, Romania banned asbestos in 2007. Romania did not extract massive amounts of asbestos; however, the country’s imports before the ban included large quantities of raw asbestos, which were later used for a wide variety of products. We have identified two peaks in the trend of raw asbestos imports, in the 1970s and the 1990s, which can be correlated to the socio-economic conditions in Romania. Lack of data availability is a real impediment to a complete estimation of the quantities of asbestos-containing products that have been used in the country. The 2007 asbestos ban did not imply the disposal of already installed such materials that could remain in place until the end of their service life. However, once removal and disposal of asbestos-containing products are needed, they come with great risks for the workers involved and the surrounding environment.